2014
DOI: 10.14356/kona.2014008
|View full text |Cite
|
Sign up to set email alerts
|

The use of Highly Ionized Pulsed Plasmas for the Synthesis of Advanced Thin Films and Nanoparticles

Abstract: Pulsed plasma processes open up the possibility of using very high plasma densities and modulated deposition in the synthesis of thin films and nanoparticles. The high plasma densities lead to a high degree of ionization of the source material, which creates new possibilities for surface engineering. Ions can, in contrast to atoms, be easily controlled with regard to their energy and direction, which is beneficial for thin film growth. Furthermore, ions can also increase the trapping probability of material on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…The influence of the modulated signal on nanoparticle formation has previously been considered in several studies. [34,35] Verdeyen et al showed that the amount of dust formation in SiH 4 plasma with pulse modulation is much lower than in continuous plasma. [36] Lloret et al used modulated RF discharge for the deposition of thin films of amorphous silicon and found that the modulation frequency had a strong effect on the porosity and roughness of films, and explained it by the effects of modulation on the nanoparticles formed in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the modulated signal on nanoparticle formation has previously been considered in several studies. [34,35] Verdeyen et al showed that the amount of dust formation in SiH 4 plasma with pulse modulation is much lower than in continuous plasma. [36] Lloret et al used modulated RF discharge for the deposition of thin films of amorphous silicon and found that the modulation frequency had a strong effect on the porosity and roughness of films, and explained it by the effects of modulation on the nanoparticles formed in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Влияние модулированного сигнала на формирование наночастиц ранее рассматривались в нескольких исследованиях [23,24]. Verdeyen и др.…”
Section: Introductionunclassified
“…Since the seminal work of Haberland's group [12,13], magnetron based ion cluster sources (ICS), also known as Gas Aggregation Sources have gained in popularity, essentially due to the fact that they are commercially available, relatively easy to use and that most of the produced NPs are charged, which allows their electrostatic manipulation for deflection of mass filtering for example. Several modifications of the original design have been reported in the literature including the use of hollow cathodes [14][15][16][17][18][19][20] and multiple cathodes [21][22][23][24][25]. They are mainly used in straight direct current (DC) and radio frequency (RF) modes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the growth rates for thin films are more difficult to control in comparison to the DC mode [35] can explain the limited number of studies of NPs synthesis using HiPIMS. So far, the pulsed mode has been used to prepare TiO x , Cu [20,[26][27][28] and Ag [29] clusters and the HiPIMS mode for the growth of Cu and Ag ones [16,17,19,29,31]. In all these studies, pure single element sputtering targets were used and studies using alloyed targets, to the best of our knowledge, have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%